Overweight/obesity and socioeconomic status in children from Aden governorate, Yemen, 2009. - Mohammed Ali Hussein Badi; Bárbara Elena García Triana; René Suárez Martínez (Universidad de Ciencias Médicas de La Habana, 2013)
Introduction: Overweight and obesity are escalating health problems in both developed and developing countries. Objective: To verify whether overweight/obesity    is related   to socioeconomic status among primary school children in Aden Governorate, Yemen. Methods: A cross-sectional study was performed on 1885 students, 6-16 years old, during 2009, selected by using multistage stratified random sampling technique. Body weight and height were measured directly; percentiles were identified for body mass index, based on the new World Health Organization growth reference standards, 2007. A survey to the parents was applied to establish the socioeconomic status through the variables: type of school, family income per capita and educational level of parents. Results: The prevalence of wasted was 10.1%, normal-weight 69.2%, overweight 12.7%, and obese 8.0%. There were statistically significant relationships between overweight/obesity and private school and high family income per capita. The prevalence of overweight/obesity was higher in children with high educational level of parents. Conclusions: Overweight/obesity in primary school children from Aden Governorate, Yemen  is related to private school, high family income per capita and probably also to high educational level of parents. More research is needed on the influence of socioeconomic factors in children obesity in the country, which is essential to set up effective prevention policies.